Original delayed-start ovarian stimulation protocol with a gonadotropin-releasing hormone antagonist, medroxyprogesterone acetate, and high-dose gonadotropin for poor responders and patients with poor-quality embryos - Takeuchi, Kazuhiro; Orita, Yuji; Iwakawa, Tokiko; Kuwatsuru, Yukari; Kuroki, Yuko; Fukumoto, Yumiko; Mizobe, Yamato; Tokudome, Mari; Moewaki, Harue (Frontiers in Endocrinology, 2023)
Low response to ovarian stimulation is a crucial problem in poor responders and patients with poorquality embryos. The delayed-start gonadotropin-releasing hormone antagonist protocol seems effective for poor responders to overcome this problem, but there are insufficient data on whether it is also effective for patients with poor-quality embryos. This study described the efficiency of this protocol for both poor responders and patients with poor-quality embryo. This protocol increased the number of MⅡ oocytes retrieved, 2PN zygotes, good blastocysts, and lead to improve live birth rates in both poor responders and patients with poor-quality embryos. It is certain that administration of GnRH antagonist contribute to synchronized follicular development and increase the number of mature oocyte. In addition, this study indicates that administration of GnRH antagonist in early follicular phase improve the quality of the oocyte.